Plasma level of big endothelin-1 predicts the prognosis in patients with hypertrophic cardiomyopathy. (15th September 2017) - Wang, Yilu; Tang, Yida; Zou, Yubao; Wang, Dong; Zhu, Ling; Tian, Tao; Wang, Jizheng; Bao, Jingru; Hui, Rutai; Kang, Lianming; Song, Lei; Wang, Ji
Abstract: Background: Cardiac remodeling is one of major pathological process in hypertrophic cardiomyopathy (HCM). Endothelin-1 has been linked to cardiac remodeling. Big endothelin-1 is the precursor of endothelin-1. Methods: A total of 245 patients with HCM were enrolled from 1999 to 2011 and partitioned to low, middle and high level groups according to their plasma big endothelin-1 levels. Results: At baseline, significant associations were found between high level of big endothelin-1 and left atrium size, heart function and atrial fibrillation. Big endothelin-1 was positively correlated with N-terminal B-type natriuretic peptide ( r  = 0.291, p  < 0.001) and late gadolinium enhancement (LGE) on magnetic resonance imaging ( r  = 0.222, p  = 0.016). During a follow-up of 3 (range, 2–5) years, big endothelin-1 level was positively associated with the risks of all-cause mortality, cardiovascular death and progression to NYHA class 3 or 4 ( p  = 0.020, 0.044 and 0.032, respectively). The rate of above events in the highest tertile were 18.1%, 15.7%, 24.2%, respectively. After adjusting for multiple factors related to survival and cardiac function, the significance remained in the association of big endothelin-1 with the risk of all-cause mortality (hazard ratio (HR) = 4.94, 95% confidence interval (CI) 1.07–22.88; p  = 0.041) and progression to NYHA class 3 or 4 (HR = 4.10, 95%CI 1.32–12.75, p  = 0.015). Conclusion: Our study showed that high level of plasma big endothelin-1 predicted prognosis for patients with HCM and it can be added to the marker panel in stratifying HCM patients for giving treatment priority to those at high risk.